FAKTOR RESIKO YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS DI RSUD UNGARAN JAWA TENGAH - Sri Wahyuni; Ngadiyono Ngadiyono; Sri Sumarni (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
The maternal mortality rate one of them caused by abortion is 15-50%.. Abortion (miscarriage) is bleeding that can lead to termination of pregnancy. Factors which are suspected predisposing factors eg abortion of the fetus, maternal factors, environmental factors, age, parity, work and history of abortion. The results of a preliminary survey conducted in hospitals Ungaran researchers obtained data is abortion in 2015, there were 245 cases The aims of this study is to determine the risk factors that influence the incidence of abortion at Ungaran hospitals. This study is a correlative study, with retrospective design. The population that was used in this research was all first trimester pregnant women who were treated at Ungaran hospitals. They experienced abortion during Januari to Desember 2015. The total number who recruited were 245 pregnant women as a total sample. The univariate analysis with frequency distribution and bivariate using Kruskal Walis Test were usedThere is no relationship between maternal age with the incidence of abortion (p=0.349 0.05) No relationship between parity with the incidence of abortion (p=0.826 0.05). There was no relationship between the working status with the incidence of abortion (p=0.114 0.05). There is a relationship between the history of the abortion with the incidence of abortion at Ungaran hospital (p=0.022 0.05), with a coefficient correlation value of 1.6. No relationship between maternal age, parity and working status with the incidence of abortion. However, history of abortion is a risk factor to be the incidence of abortion with a 1.6 times greater than those who don’t have history of abortion. Midwives are expected to anticipate the incidence of abortion by further improving supervision, especially to pregnant women with risk factors for abortion.